2018
DOI: 10.1002/admt.201800569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Atmosphere on the Performance of Contact–Separation Mode TENG

Abstract: With great potential applications, triboelectric nanogenerator (TENG), is widely studied from various aspects, while systematic investigations about the effects of environmental atmosphere on its performance remain to be carried out. Here, a test system based on a piston‐structured TENG and one‐way valve gas line is built, employing the contact–separation mode. A series of tests about short‐circuit transfer charges (QSC) and open‐circuit voltage (VOC) are studied among three kinds of dielectric materials (PTFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
1
17
2
Order By: Relevance
“…It was found that the dielectric material can gain more electrons due to the chemical bond formed between O 2 and the dielectric material. 7 On the contrary, in our research CE performance is lowered. We anticipate that the chemical bond between O 2 and the polymer cannot be formed under the low O 2 concentration, in which the influence mechanism on CE is similar to that of O 3 .…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…It was found that the dielectric material can gain more electrons due to the chemical bond formed between O 2 and the dielectric material. 7 On the contrary, in our research CE performance is lowered. We anticipate that the chemical bond between O 2 and the polymer cannot be formed under the low O 2 concentration, in which the influence mechanism on CE is similar to that of O 3 .…”
Section: Resultscontrasting
confidence: 67%
“…In the previous work, CE was performed at the pure O 2 condition between Pt/Ir and dielectrics. It was found that the dielectric material can gain more electrons due to the chemical bond formed between O 2 and the dielectric material . On the contrary, in our research CE performance is lowered.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…These factors could considerably stagnate the TECD value. Additionally, there is a chance for the generated TECD to be lost by air breakdown, combining with induced charges and other particles, and finally electron emission . Theoretically, in a capacitive model, we could calculate the TECD (σ) under open-circuit conditions as eq …”
Section: Resultsmentioning
confidence: 99%
“…The TEGs that can work under low accelerating frequency pave the way for its application in a wide range and also in many fields such as energy harvesting (wind, water wave, mechanical, and biomechanical), sensing applications such as physical sensors, human motion monitoring, , wind vector monitoring, and direction monitoring . Also, TEGs can be used as a chemical sensor by detecting various chemical analytes, humidity, liquid sensing, and phenols . As a water wave energy harvester, TEGs have been utilized with various upgrades such as TEG devices with high performance and TEGs with electromagnetic generator (TEG-EMG) hybrid devices, and device structures such as spheroidal buoy shape and oblate spheroidal shape, butterfly-inspired water wave energy harvester, ship-shaped hybrid type, and roll-swing oscillator type are reported.…”
Section: Introductionmentioning
confidence: 99%